Le « zéro déchet », tou(te)s dans le même bocal ? Profils, pratiques, et formes d’engagement - Marie Mourad; Florian Cezard; Steve Joncoux (VertigO)
Two sociologists and a consultant in sustainability offer a reflection on the survey “Living well with Zero Waste” that they carried out for the French Environmental Agency (ADEME) in 2016. By analyzing the profiles of 643 people who identify as being “Zero Waste” and through ethnographic observations of the daily practices and engagements of 12 households, they show how the word “Zero Waste” brings together people with a variety of motivations, practices, and social profiles—despite a majority of young women from privileged backgrounds. These Zero Waste households support social change and progressively serve as a leverage for environmental institutions to act. Yet, this Zero Waste mobilization does not resolve some social issues, such as the unequal repartition of wealth and work.